Total Analysis of the Major Secoiridoids in Extra Virgin Olive Oil: Validation of an UHPLC-ESI-MS/MS Method - Julián Lozano-Castellón; Anallely López-Yerena; Alexandra Olmo-Cunillera; Olga Jáuregui; Maria Pérez; Rosa Mª Lamuela-Raventós; Anna Vallverdú-Queralt (MDPI AG, 2021)
Extra virgin olive oil (EVOO), one of the key foods of the Mediterranean diet, is distinguished by its high content of nutritional and antioxidant compounds compared to other vegetable oils. During EVOO production, the major secoiridoids of EVOO, oleacein, oleocanthal, ligstroside, and oleuropein aglycones, undergo a series of transformations to open- and closed-structure forms. The resulting mixture of compounds can become more complex during the analytical procedure, due to the keto-enol tautomerism of the open forms and their interaction with polar solvents, and therefore more challenging to analyze. Employing the same extraction method used to analyze the other EVOO phenolic compounds, we report here a simple UHPLC-ESI-MS/MS procedure for the quantification of those secoiridoids that is able to co-elute the different isomers of each compound. The method was validated following AOAC guidelines, and the matrix effect and recoveries were within satisfactory limits.